Pendampingan Literasi Kitab Kuning dan Penulisan Ringkasan Berbahasa Indonesia bagi Santri Madrasah Aliyah Ma’arif 7 Sunan Drajat - Wanto, Wanto (Jaanur ElBarik Indonesia, 2025)
Mastery of the yellow book is an important competency for students in understanding classical Islamic literature which is the foundation of Islamic thought and law. However, limited understanding of the structure of classical Arabic and the lack of ability to rewrite the contents of the book in good Indonesian are often obstacles for middle-level students. This community service activity aims to assist students in improving their literacy of the yellow book and their skills in writing summaries of the contents of the book in communicative and systematic Indonesian. The methods used are practice-based training, structured discussions, and tiered assignments carried out over six meetings. The results of the activity showed an increase in students' understanding of the contents of the book and their ability to express this understanding in the form of a summary in Indonesian. This program is expected to become a model for mentoring yellow book literacy that is applicable and contextual for other Islamic boarding school educational institutions.